Clinical Characteristics of Highly Myopic Patients With Asymmetric Myopic Atrophic Maculopathy–Analysis Using Multimodal Imaging - Hsia, Yun (Invest Ophthalmol Vis Sci, 2021)
PURPOSE: To evaluate the factors associated with asymmetric myopic atrophic maculopathy (MAM) in highly myopic patients. METHODS: We enrolled highly myopic patients with asymmetric MAM according to the atrophy, traction, and neovascularization (ATN) classification. The results of color fundus photography, optical coherence tomography (OCT), OCT angiography, and corneal visualization Scheimpflug technology (Corvis ST tonometry) were reviewed. The association between inter-eye differences in clinical features and MAM grading was analyzed using logistic regression analysis. RESULTS: Among the 72 eyes of 36 patients 61.0 ± 9.3 years of age, 9, 33, 17, and 13 eyes had A1, A2, A3, and A4, respectively. The mean axial length was 30.44 ± 1.92 mm, and there was no significant difference between eyes with less severe and more severe MAM. The inter-eye differences in MAM grading were associated with the inter-eye differences in the presence of Bruch's membrane defects (P = 0.014), ellipsoid zone disruption (P = 0.013), vessel density of the deep retinal layer (P = 0.022), foveal avascular zone circularity (P = 0.012), foveal avascular zone area (P = 0.049), flow area of the choriocapillaris (P = 0.013), vessel diameter (P = 0.045), and fractal dimension (P = 0.015). No Corvis ST parameter was statistically significant. A higher difference in the choriocapillaris flow area (P = 0.013; adjusted odds ratio = 1.10 [1.02–1.18]) remained associated with higher inter-eye differences in MAM grading in the multivariable regression. CONCLUSIONS: A smaller choriocapillaris flow area was associated with more severe MAM, suggesting that vascular factors play pivotal roles in MAM.